El rol del delegado de protección de datos en Europa tras la aprobación del Reglamento UE de Inteligencia Artificial - Martínez Gutiérrez, Rubén (2025)
Data Protection Officers in the European Union are undergoing a period of increasing change in terms of their legal status and functions, as a result of new regulations on data, interoperability and Artificial Intelligence. These changes particularly affect the public sector, which will be analysed specifically in this paper. This article analyses the essential functions of DPOs derived from data protection regulations, as well as those that are expected to be added as a result of the new EU regulatory framework, with a particular focus on the supervision of sandboxes and impact assessments on fundamental rights in artificial intelligence.